The emergence of Gallicism in military terminology in the English and the Uzbek languages - Kenjaeva Zukhra (Genius Journals, 2022)
The present article focuses on the history of the emergence of military terms such as Gallicism that were borrowed from French to English and Uzbek as a result of various armed conflicts and military contacts throughout certain historical periods. In particular, the influence of Gallicism enriched lexical units of the receiving language, especially in the sphere of military vocabulary for words describing military terms as well as military ranks. Different loanwords from old French, middle French, and modern French are reviewed and analyzed. The paper concludes by emphasizing that borrowing French words is a dynamic linguistic phenomenon that plays a key role in the evolution of English and Uzbek military terms and slang phrases.
Keywords: Military Vocabulary; Military Terms; Gallicism; Loanwords